ANALYSIS OF EMPOWERMENT MODELS FACTORS OF SMALL AND MEDIUM ENTERPRISES (SME) COMMUNITY FACTORS TO IMPROVING COMMUNITY WELFARE - Desy Roa; Anuar Sanusi (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Development has a dynamic nature, continues to develop and process. One of the development focuses of a society or country is Community Development. That assumption appears based on the fact that society continues to develop and process, therefore there should be a dynamic Community Development Model that can assist the community development process. This study aims to describe tangible and intangible factors for the community empowerment model. Through tangible factor variables (physical capital, human capital, social capital, financial capital, environmental capital and intangible factor variables (motivation, trust, mentoring) can increase empowerment which has implications for the level of community welfare. The method used is descriptive method using Structural Equation Modeling (SEM). To find out which tangible and intangible factors can improve empowerment which has implications for the level of understanding of the community, the method used to solve problems. Tangible and intangible factors that are significant are good or strategic factors to empower the community. while the most dominant factor is the variable of physical capital with a total effect of 0.312 on empowerment compared to the others. this is because its influence on empowerment is very dominant. and variables that have the greatest total effect on welfare are assistance variables with a total effect of 0.416. this is due to its dominant influence on welfare.Keywords: Tangible, Intangible Factor , Empowerment, Community Welfare.